Lithium secondary battery comprising electrolyte

By adding bifunctional electrolyte additives and additives containing more than two fluorine-based groups to the electrolyte of the lithium secondary battery, the problem that when using the silicon-based negative electrode of the lithium secondary battery is difficult to achieve high capacity, fast charging, low battery resistance and good high-temperature cycling performance at the same time, and the improvement of battery performance and the reduction of gas production are achieved.

CN119547247APending Publication Date: 2025-02-28LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380056539.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-22
Filing Date
2023-12-25
Publication Date
2025-02-28

Smart Images

  • Figure CN119547247A_ABST
    Figure CN119547247A_ABST
Patent Text Reader

Abstract

The present application relates to a lithium secondary battery comprising a positive electrode, a silicon-based negative electrode, a separator, and an electrolyte, in which a negative electrode active material layer of the silicon-based negative electrode comprises a silicon-based active material, the electrolyte comprises an additive comprising a bifunctional electrolyte additive and an additive comprising two or more fluorine groups, the bifunctional electrolyte additive contains a cyano group and a coumarin group as functional groups, and the content of the bifunctional electrolyte additive is 45 parts by weight or more and 55 parts by weight or less based on 100 parts by weight of the additive, and the content of the additive containing two or more fluorine groups is 45 parts by weight or more and 55 parts by weight or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0187442 filed in the Korean Intellectual Property Office on December 28, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a lithium secondary battery including an electrolyte. Background Art

[0003] Because the use of fossil fuels has increased rapidly, the demand for the use of alternative or clean energy has been increasing, and as part of this trend, the most active field of research is the field of power generation and storage using electrochemical reactions.

[0004] Currently, representative examples of electrochemical devices using such electrochemical energy include secondary batteries, and their use fields are increasing.

[0005] With the technological development and increase in demand of mobile devices, the demand for secondary batteries as energy sources has increased rapidly. Among these secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as an electrode for such a high-capacity lithium secondary battery, a method for preparing a high-density electrode with higher energy density per unit volume has been actively studied.

[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material that intercalates and deintercalates lithium ions from the positive electrode, and carbon-based materials such as graphite have excellent stability and reversibility as negative electrode materials, but have limitations in capacity, so in the field of achieving high capacity, more and more attempts are made to use Si-based materials with high theoretical capacity as negative electrode materials.

[0007] That is, lithium secondary batteries are usually manufactured using lithium-embedded compounds such as LiCoO2 and LiMn2O4 for the positive electrode and non-lithium-embedded materials such as carbon and Si materials for the negative electrode, and during charging, the lithium ions embedded in the positive electrode move to the negative electrode through the electrolyte, and during discharge, the lithium ions move from the negative electrode to the positive electrode. The lithium that moves from the positive electrode to the negative electrode during the charging reaction reacts with the electrolyte to form a solid electrolyte interface (SEI) as a passivation film on the surface of the negative electrode. The SEI can stabilize the structure of the negative electrode by inhibiting the movement of electrons required for the reaction between the negative electrode and the electrolyte to prevent the decomposition reaction of the electrolyte, but because the reaction is an irreversible reaction, lithium ions are consumed. That is, the lithium consumed due to the formation of SEI does not return to the positive electrode during the subsequent discharge process, thereby reducing the capacity of the battery.

[0008] On the other hand, in order to improve the performance of lithium secondary batteries, it is necessary to develop technologies to increase the charging speed. Because in order to quickly charge lithium secondary batteries, the movement speed of lithium ions is required to be fast during the process of lithium ion embedding into the negative electrode, so it is necessary to form a negative electrode active material layer as thick as a film to shorten the diffusion distance of lithium, and form a carbon coating on the surface to increase conductivity and reduce internal resistance, so as to design a battery that achieves high output.

[0009] However, it is difficult to achieve high capacity using a negative electrode including such a thin film negative electrode active material layer. In addition, it is difficult to achieve fast charging using a negative electrode that achieves high capacity. In addition, when a silicon-based negative electrode is used, the Si content of the negative electrode increases due to the increase in energy density, thereby reducing the efficiency of the high Ni positive electrode as a positive electrode material, and for this reason, an excessive amount of sacrificial positive electrode material is applied to achieve a balance with the negative electrode, but in this case, the amount of gas in the battery cell itself increases, resulting in stability problems.

[0010] Therefore, research is required to be conducted to be able to maintain battery resistance while achieving high capacity using a negative electrode including a silicon-based active material, improve high temperature cycle performance, and reduce the amount of gas generated during storage.

[0011] Related technical literature

[0012] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention

[0013] [Technical issues]

[0014] As a result of research on the above-mentioned problems, when a silicon-based negative electrode is used to ensure capacity characteristics and fast charging performance and an additive having a predetermined composition and content is included in the electrolyte at the same time, a method is obtained that can maintain battery resistance, improve high-temperature cycle performance and reduce the amount of gas generated during storage.

[0015] Therefore, the present application relates to a lithium secondary battery, which includes: a silicon-based negative electrode; and an electrolyte containing a specific additive.

[0016] [Technical solution]

[0017] An exemplary embodiment of the present specification provides a lithium secondary battery, the lithium secondary battery including:

[0018] positive electrode;

[0019] Silicon-based negative electrode;

[0020] a separator disposed between the positive electrode and the negative electrode; and

[0021] Electrolytes,

[0022] Wherein the silicon-based negative electrode comprises: a negative electrode current collector layer; and a negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer,

[0023] The negative electrode active material layer comprises a negative electrode active material layer composition,

[0024] The negative electrode active material layer composition comprises a silicon-based active material, and the silicon-based active material comprises one or more selected from SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloys,

[0025] The electrolyte comprises an additive,

[0026] The additive comprises: a bifunctional electrolyte additive; and an additive containing two or more fluorine groups,

[0027] The bifunctional electrolyte additive comprises a cyano group and a coumarin group as functional groups, and

[0028] Based on 100 parts by weight of the additive, the content of the bifunctional electrolyte additive is 45 parts by weight or more and 55 parts by weight or less, and the content of the additive containing two or more fluorine groups is 45 parts by weight or more and 55 parts by weight or less.

[0029] [Advantageous Effects]

[0030] The lithium secondary battery according to the present application uses a silicon-based negative electrode and can ensure high capacity and high energy density of the battery. Moreover, since a silicon-based active material with excellent capacity characteristics is used, the negative electrode is formed to have a thickness like that of a thin film, so fast charging performance can also be ensured.

[0031] In particular, the lithium secondary battery according to the present application is characterized in that it contains specific additives in the electrolyte. Specifically, the electrolyte contains a bifunctional electrolyte additive, which can be used to capture the Lewis acid generated by the solvent contained in the electrolyte and form a negative electrode film when driving the lithium secondary battery. In addition, the electrolyte contains an additive containing two or more fluorine groups as an additive, so that the battery resistance can be maintained while the high-temperature cycle performance can be improved.

[0032] As described above, it is characterized in that by including specific additives in the electrolyte, the battery resistance can be maintained while driving the lithium secondary battery, the high-temperature cycle performance can be improved, and the amount of gas generated during storage can be reduced.

[0033] In addition, the electrolyte according to the present application contains a bifunctional electrolyte additive having the above characteristics and an additive containing two or more fluorine groups as additives, and the content of the bifunctional electrolyte additive is 45 parts by weight or more and 55 parts by weight or less based on 100 parts by weight of the additive, and the content of the additive containing two or more fluorine groups is 45 parts by weight or more and 55 parts by weight or less. Therefore, it is also characterized in that the battery resistance can be kept from increasing while preventing the dissolution of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a view showing a lithium secondary battery according to the present application.

[0035] <Reference Numbers>

[0036] 10: Negative electrode collector layer

[0037] 20: Negative electrode active material layer

[0038] 30: Diaphragm

[0039] 40: Positive electrode active material layer

[0040] 50: Positive electrode collector layer

[0041] 100: Negative electrode

[0042] 200: Positive DETAILED DESCRIPTION

[0043] Before describing the present invention, some terms are first defined.

[0044] In the present specification, when a part “comprises” a constituent element, unless otherwise specifically stated, this does not mean that another constituent element is excluded but means that another constituent element may further be included.

[0045] In this specification, "p to q" means a range of "p or more and q or less".

[0046] In this specification, the "specific surface area" is measured by the BET method, specifically, calculated from the nitrogen adsorption at liquid nitrogen temperature (77 K) using BELSORP-mini II manufactured by BEL Japan, Inc. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the measurement method.

[0047] In this manual, "D n " refers to the particle size distribution, and refers to the particle size at the n% point of the cumulative distribution of the number of particles according to the particle size. That is, D 50 is the particle size at the 50% point of the cumulative distribution of particle numbers according to particle size, D 90is the particle size at the 90% point of the cumulative distribution of particle numbers according to particle size, and D 10 It is the particle size at the 10% point of the cumulative distribution of the number of particles according to the particle size. On the other hand, the particle size distribution can be measured using a laser diffraction method. Specifically, after the powder to be tested is dispersed in a dispersion medium, the particle size distribution is calculated by introducing the resulting dispersion into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the change in the diffraction pattern with the particle size when the particles pass through the laser beam.

[0048] In the present specification, the fact that a polymer contains a monomer as a monomer unit means that the monomer participates in a polymerization reaction and is therefore contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, it is interpreted as the same as when the polymer contains a monomer as a monomer unit.

[0049] In this specification, "polymer" is understood to be used in a broad sense, including copolymers, unless otherwise specified as a "homopolymer".

[0050] In this specification, the weight average molecular weight (M w ) and number average molecular weight (M n ) is a polystyrene-converted molecular weight measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specified, molecular weight refers to weight average molecular weight.

[0051] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.

[0052] An exemplary embodiment of the present specification provides a lithium secondary battery, which includes: a positive electrode; a silicon-based negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the silicon-based negative electrode includes: a negative electrode current collector layer; and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode current collector layer, the negative electrode active material layer includes a negative electrode active material layer composition, the negative electrode active material layer composition includes a silicon-based active material, the silicon-based active material includes one or more selected from SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloys, the electrolyte includes an additive, the additive includes: a bifunctional electrolyte additive; and an additive containing two or more fluorine groups, the bifunctional electrolyte additive includes a cyano group and a coumarin group as functional groups, and based on 100 parts by weight of the additive, the content of the bifunctional electrolyte additive is 45 parts by weight or more and 55 parts by weight or less, and the content of the additive containing two or more fluorine groups is 45 parts by weight or more and 55 parts by weight or less.

[0053] As described above, it is characterized in that by including a specific additive in the electrolyte, the battery resistance can be maintained during the driving of the lithium secondary battery, while improving the high-temperature cycle performance and reducing the amount of gas generated during storage.

[0054] Figure 1 A view showing the stacked structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, it can be confirmed that the negative electrode 100 includes a negative electrode active material layer 20 on one surface of the negative electrode current collector layer 10, and it can be confirmed that the positive electrode 200 includes a positive electrode active material layer 40 on one surface of the positive electrode current collector layer 50, and it is shown that the negative electrode 100 and the positive electrode 200 of the lithium secondary battery are formed in a stacked structure in which an electrode is disposed therebetween with a separator 30 interposed therebetween.

[0055] Hereinafter, the positive electrode, negative electrode, electrolyte, and separator included in the lithium secondary battery will be described separately.

[0056] An exemplary embodiment of the present application provides a lithium secondary battery, wherein the electrolyte includes an additive, the additive includes: a bifunctional electrolyte additive; and an additive containing two or more fluorine groups, and based on 100 parts by weight of the additive, the content of the bifunctional electrolyte additive is 45 parts by weight or more and 55 parts by weight or less, and the content of the additive containing two or more fluorine groups is 45 parts by weight or more and 55 parts by weight or less.

[0057] Specifically, the lithium secondary battery according to the present application is characterized in that a specific additive is included in the electrolyte. Specifically, the electrolyte contains a bifunctional electrolyte additive that can be used to capture Lewis acids generated by solvents contained in the electrolyte and can be used to form a negative electrode film when driving the lithium secondary battery. In addition, the electrolyte contains an additive containing two or more fluorine groups as an additive, so that the battery resistance can be maintained and the high temperature cycle performance can be improved.

[0058] An exemplary embodiment of the present application provides a lithium secondary battery, wherein a bifunctional electrolyte additive includes at least a cyano group as a functional group.

[0059] In another exemplary embodiment, the bifunctional electrolyte additive may include at least a cyano group as a functional group, specifically, the bifunctional electrolyte additive may include at least a cyano group or a coumarin group as a functional group, more specifically, the bifunctional electrolyte additive may include a cyano group and a coumarin group as functional groups.

[0060] In an exemplary embodiment of the present application, the bifunctional electrolyte additive may be 6-cyanocoumarin.

[0061] Since a specific functional group is contained as the functional group as described above, it is characterized in that it can be used to capture Lewis acid generated from a solvent contained in an electrolyte and form a negative electrode film.

[0062] An exemplary embodiment of the present application provides a lithium secondary battery, wherein the additive including two or more fluorine groups is: a lithium borate including two or more fluorine groups; or a lithium phosphate including two or more fluorine groups.

[0063] The additive including two or more fluorine groups is an additive capable of reducing battery resistance, and is used to maintain battery resistance and improve high temperature cycle performance at the same time.

[0064] In an exemplary embodiment of the present application, the additive including two or more fluorine groups may include: lithium fluoromalonate (difluoro)borate; lithium difluorophosphate; or lithium difluorobis(oxalato)phosphate.

[0065] An exemplary embodiment of the present application provides a lithium secondary battery, wherein the content of the additive is 5 parts by weight or less based on 100 parts by weight of the electrolyte.

[0066] In another exemplary embodiment, the content of the additive may be 5 parts by weight or less, preferably 4 parts by weight or less, more preferably 3 parts by weight or less, and may be 0.5 parts by weight or more, specifically 1 part by weight or more, based on 100 parts by weight of the electrolyte.

[0067] An exemplary embodiment of the present application provides a lithium secondary battery, wherein the content of the bifunctional electrolyte additive is 45 parts by weight or more and 55 parts by weight or less, and the content of the additive including two or more fluorine groups is 45 parts by weight or more and 55 parts by weight or less, based on 100 parts by weight of the additive.

[0068] In another exemplary embodiment, the content of the bifunctional electrolyte additive may be 45 parts by weight or more and 55 parts by weight or less, preferably 47 parts by weight or more and 53 parts by weight or less, based on 100 parts by weight of the additive.

[0069] In yet another exemplary embodiment, the content of the additive including two or more fluorine groups may be 45 parts by weight or more and 55 parts by weight or less, preferably 47 parts by weight or more and 53 parts by weight or less, based on 100 parts by weight of the additive.

[0070] In an exemplary embodiment of the present application, the additive includes: a bifunctional electrolyte additive; and an additive including two or more fluorine groups, and a weight ratio of the bifunctional electrolyte additive: the additive including two or more fluorine groups may be 1:0.8 to 1:1.2.

[0071] In another exemplary embodiment, a weight ratio of the bifunctional electrolyte additive: the additive including two or more fluorine groups may satisfy 1:0.8 to 1:1.2, specifically 1:0.9 to 1:1.1, and more specifically 1:1.

[0072] The electrolyte according to the present application is characterized in that it contains an additive having the composition and content. Therefore, it is also characterized in that the battery resistance can be kept from increasing while preventing the electrolyte from dissolving. That is, when the weight ratio exceeds the above ratio, the battery resistance becomes too high, and the solubility of the additive containing two or more fluorine groups is low, so when the additive containing two or more fluorine groups is used beyond the above range, it is characterized in that because dissolution occurs in the electrolyte, the performance of the lithium secondary battery will deteriorate.

[0073] An exemplary embodiment of the present application provides a lithium secondary battery, wherein the electrolyte further includes one or more selected from a solvent and a lithium salt.

[0074] As the solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate can be used.

[0075] The present application provides a lithium secondary battery, wherein the solvent is a carbonate-based mixed solvent.

[0076] In particular, in carbonate-based mixed solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate can be preferably used because the cyclic carbonates as high-viscosity organic solvents have a high dielectric constant, thereby dissociating lithium salts well. When the cyclic carbonates are mixed with linear carbonates of low viscosity and low dielectric constant such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, an electrolyte with high conductivity can be prepared, so such a combined use is more preferred.

[0077] The lithium salt is a material that is easily soluble in a non-aqueous electrolyte. For example, as the anion of the lithium salt, one or more selected from the following can be used: - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - 、PF6-、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2- 、SCN - and (CF3CF2SO2)2N - .

[0078] In the electrolyte, in order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and increase the discharge capacity of the battery, on the basis of containing the above-mentioned electrolyte components, for example, one or more additives such as the following may be included: halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0079] The silicon-based negative electrode according to the present application may include: a negative electrode current collector layer; and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode current collector layer.

[0080] The negative electrode collector layer generally has a thickness of 1 μm to 100 μm. The negative electrode collector layer is not particularly limited as long as it has high conductivity and does not cause chemical changes to the battery, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon; copper or materials whose surfaces have been treated with carbon, nickel, titanium, silver, etc.; aluminum-cadmium alloy, etc. In addition, the negative electrode collector layer can also improve the bonding strength of the negative electrode active material by forming fine concave-convex on its surface, and the negative electrode collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0081] However, the thickness may be variously modified according to the type and purpose of the negative electrode used, and is not limited thereto.

[0082] In an exemplary embodiment of the present application, the negative electrode active material layer includes a negative electrode active material layer composition, and the negative electrode active material layer composition may include a silicon-based active material.

[0083] In an exemplary embodiment of the present application, the negative electrode active material layer includes a negative electrode active material layer composition, and the negative electrode active material layer composition may include one or more selected from the group consisting of a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.

[0084] In an exemplary embodiment of the present application, the negative electrode active material layer includes a negative electrode active material layer composition, and the negative electrode active material layer composition may include: a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.

[0085] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloys.

[0086] In an exemplary embodiment of the present application, the silicon-based active material includes one or more selected from SiOx (x = 0), SiOx (0 < x < 2), and metal impurities, and based on 100 parts by weight of the silicon-based active material, it may include 70 parts by weight or more of SiOx (x = 0).

[0087] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more, preferably 80 parts by weight or more and more preferably 90 parts by weight or more, and the content may be 100 parts by weight or less, preferably 99 parts by weight or less and more preferably 95 parts by weight or less.

[0088] In an exemplary embodiment of the present application, for the silicon-based active material, in particular, pure silicon (Si) may be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that based on the total 100 parts by weight of the silicon-based active material as described above, pure silicon particles (SiOx (x = 0)) not bound to other particles or elements are included in the above range.

[0089] On the other hand, the silicon-based active material of the present invention may have an average particle size (D 50 ) of 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is less than 5 μm, the specific surface area of the particles increases excessively, resulting in an excessive increase in the viscosity of the negative electrode slurry. Therefore, the particles constituting the negative electrode slurry cannot be smoothly dispersed. In addition, when the size of the silicon-based active material is too small, the contact area between the silicon particles and the conductive material in the composite material composed of the conductive material and the binder in the negative electrode slurry decreases, increasing the possibility of damage to the conductive network, thereby reducing the capacity retention rate. On the other hand, when the average particle size is greater than 10 μm, there will be excessively large silicon particles, making the negative electrode surface uneven, and thus resulting in uneven current density during charging and discharging. In addition, when the silicon particles are too large, the processing performance deteriorates because the phase stability of the negative electrode slurry becomes unstable. Therefore, the capacity retention rate of the battery deteriorates.

[0090] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably 0.01 m 2 / g to 150.0 m 2 / g, more preferably 0.1 m2 / g to 100.0 m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m 2 / g, and most preferably 0.2 m 2 / g to 18.0 m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen).

[0091] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a film or coating containing silicon.

[0092] In an exemplary embodiment of the present application, the content of the silicon-based active material may be 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.

[0093] In another exemplary embodiment, based on 100 parts by weight of the negative electrode active material layer composition, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less.

[0094] The negative electrode active material layer composition according to the present application is characterized in that by using a specific negative electrode conductive material and a specific negative electrode binder, even if a silicon-based active material with a very high capacity is used within the above range, the volume expansion rate during charging and discharging can be suppressed, and the performance of the negative electrode will not deteriorate even when the content is within the above range, and the output characteristics during charging and discharging are also excellent.

[0095] In an exemplary embodiment of the present application, the silicon-based active material may have a non-circular form, and the circularity thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0096] In the present application, circularity is determined by the following Formula 1, where A is the area and P is the boundary line perimeter.

[0097] [Formula 1]

[0098] 4πA / P 2

[0099] In the prior art, only graphite compounds are generally used as negative electrode active materials, but in recent years, as the demand for high-capacity batteries increases, attempts to mix and use silicon compounds to increase capacity have increased. However, in the case of silicon compounds, there is a limitation that the volume expands rapidly during the charge / discharge process and damages the conductive path formed in the negative electrode active material layer, thereby causing the performance of the battery to deteriorate.

[0100] Therefore, in an exemplary embodiment of the present application, the negative electrode active material layer composition may include a negative electrode conductive material and a negative electrode binder. That is, the negative electrode conductive material is used to ensure a conductive path, and the binder is used to maintain the negative electrode conductive material during charge and discharge.

[0101] In an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a surface-shaped conductive material, and a line-shaped conductive material.

[0102] In an exemplary embodiment of the present application, a dot-shaped conductive material can be used to enhance the conductivity of the negative electrode, and the dot-shaped conductive material refers to a conductive material that forms conductivity without causing chemical changes, and refers to a conductive material whose morphology is circular or dot-shaped. Specifically, the dot-shaped conductive material can be at least one selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and in terms of achieving high conductivity and excellent dispersibility, carbon black may be preferably included.

[0103] In an exemplary embodiment of the present application, the dot-shaped conductive material may have a size of 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less and more preferably 50 m 2 / g and above 60 m 2 / g or less BET specific surface area.

[0104] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 40 nm to 60 nm.

[0105] In an exemplary embodiment of the present application, the conductive material may include a planar conductive material.

[0106] The planar conductive material refers to a conductive material that increases the surface contact between silicon particles in the negative electrode to improve conductivity and inhibits disconnection of the conductive path due to volume expansion. The planar conductive material can be a plate-shaped conductive material or a block-shaped conductive material.

[0107] In an exemplary embodiment of the present application, the planar conductive material may include at least one selected from plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.

[0108] In an exemplary embodiment of the present application, the planar conductive material may have an average particle size (D) of 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. 50 ). When the average particle size satisfies the above range, sufficient particle size promotes dispersion without causing excessive increase in viscosity of the negative electrode slurry. Therefore, when the same equipment and time are used to disperse the particles, the dispersion effect is excellent.

[0109] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein D of the planar conductive material 10 is 0.5 μm or more and 1.5 μm or less, D 50 is 4.0 μm or more and 5.0 μm or less, and D 90 It is 7.0 μm or more and 15.0 μm or less.

[0110] In an exemplary embodiment of the present application, as the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area; or a low specific surface area planar conductive material may be used.

[0111] In an exemplary embodiment of the present application, as the planar conductive material, a high specific surface area planar conductive material or a low specific surface area planar conductive material can be used without restriction, but in particular, the planar conductive material according to the present application may be affected to a certain extent by the dispersibility in terms of electrode performance, and therefore it may be particularly desirable to use a low specific surface area planar conductive material that will not cause problems in terms of dispersibility.

[0112] In an exemplary embodiment of the present application, the BET specific surface area of ​​the planar conductive material may be 1 m 2 / g or above.

[0113] In another exemplary embodiment, the BET specific surface area of ​​the planar conductive material may be 1 m 2 / g and above and 500m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m2 / g and above 250 m 2 / g or less.

[0114] In another exemplary embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m 2 / g or less and more preferably 100 m 2 / g and above 250 m 2 / g or less.

[0115] In another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g or more and 30 m 2 / g or less and more preferably 5m 2 / g and above 25 m 2 / g or less.

[0116] As other conductive materials, linear conductive materials such as carbon nanotubes can be cited. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" used herein refers to a secondary shape in the form of a bundle or rope, in which a plurality of carbon nanotube units are aligned side by side or are intertwined with each other in an orientation in which the longitudinal axes of the carbon nanotube units are substantially the same. In the carbon nanotube unit, the graphene sheet has a cylindrical shape with a diameter of nanometers and has a sp 2 In this case, the carbon nanotube unit can exhibit the characteristics of a conductor or a semiconductor depending on the structure and the angle of the rolled graphite sheet. Compared with the tangled carbon nanotubes, the bundled carbon nanotubes can be evenly dispersed during the preparation of the negative electrode, and can improve the conductivity of the negative electrode by smoothly forming a conductive network in the negative electrode.

[0117] In an exemplary embodiment of the present application, the negative electrode conductive material includes a linear conductive material, and the linear conductive material may be a carbon nanotube.

[0118] In an exemplary embodiment of the present application, the carbon nanotube may be SWCNT or / and MWCNT. When the linear conductive material is SWCNT, the length of the SWCNT may be 0.5 μm to 100 μm, preferably 1 μm to 80 μm.

[0119] In an exemplary embodiment of the present application, the content of the negative electrode conductive material may be 5 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode active material layer composition.

[0120] In another exemplary embodiment, the content of the negative electrode conductive material may be 5 parts by weight or more and 40 parts by weight or less, preferably 5 parts by weight or more and 30 parts by weight or less, and more preferably 5 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.

[0121] In an exemplary embodiment of the present application, the negative electrode conductive material includes a planar conductive material and a linear conductive material, and a ratio of the planar conductive material: the linear conductive material may satisfy 1:0.001 to 1:0.3.

[0122] In an exemplary embodiment of the present application, because the negative electrode conductive material includes a planar conductive material and a linear conductive material and each satisfies the composition and proportion, this will not have a great impact on the service life characteristics of the existing lithium secondary battery and increases the points at which the battery can be charged and discharged, so the negative electrode conductive material has excellent output characteristics at a high C rate.

[0123] The negative electrode conductive material according to the present application has a completely different structure from the conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application is used to capture the contact points between the silicon-based active materials in which the volume expansion of the electrode is very large due to charging and discharging, while the positive electrode conductive material is used to play a buffering role as a mitigating role during rolling while imparting partial conductivity, and its structure and role are completely different from those of the negative electrode conductive material of the present invention.

[0124] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different structure from the conductive material applied to the graphite-based active material. That is, the conductive material used for the electrode with the graphite-based active material has only small particles relative to the active material, and thus has the characteristics of improving the output characteristics and imparting partial conductivity, and its structure and function are completely different from those of the negative electrode conductive material applied together with the silicon-based active material in the present invention.

[0125] In an exemplary embodiment of the present application, the plate-shaped conductive material used as the above-mentioned negative electrode conductive material has a structure and function different from the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material that is processed into a spherical or dot shape and used in order to promote the storage and release of lithium ions.

[0126] In contrast, the plate-like conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and may be in the form of plate-like graphite. That is, the plate-like conductive material is a material contained in order to maintain the conductive path in the negative electrode active material layer, and refers to a material that ensures the conductive path in a planar form in the negative electrode active material layer, rather than playing a role in storing and releasing lithium.

[0127] That is, in the present application, the fact that plate-like graphite is used as a conductive material means that the plate-like graphite is processed into a planar or plate-like shape and used as a material that ensures a conductive path rather than playing a role of storing or releasing lithium. In this case, the negative electrode active material contained together has a high capacity characteristic for storage and release of lithium, and plays a role capable of storing and releasing all lithium ions transmitted from the positive electrode.

[0128] In contrast, in the present application, the fact that a carbon-based active material is used as an active material means that the carbon-based active material is processed into a dot shape or a spherical shape and used as a material for storing or releasing lithium.

[0129] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0130] The negative electrode binder according to an exemplary embodiment of the present application plays the role of supporting the silicon-based active material and the negative electrode conductive material to prevent the distortion and structural deformation of the negative electrode structure when the silicon-based active material undergoes volume expansion and relaxation, and when the above-mentioned role is met, all common negative electrode binders can be applied, specifically, water-based binders can be used, and more specifically, PAM-based binders can be used.

[0131] In an exemplary embodiment of the present application, based on 100 parts by weight of the negative electrode active material layer composition, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and the content may be 5 parts by weight or more, 8 parts by weight or more.

[0132] When Si-based materials are used in the negative electrode, compared with the existing carbon-based negative electrode, the use of the above-mentioned weight portion of the aqueous binder makes it possible to use a point-shaped conductive material with a low functional group content, and based on this feature, the point-shaped conductive material has hydrophobicity, thereby having the characteristic of excellent bonding strength with the conductive material / binder.

[0133] In an exemplary embodiment of the present application, a silicon-based negative electrode may be formed by coating one surface or both surfaces of a negative electrode collector layer with a negative electrode slurry including a negative electrode active material layer composition.

[0134] In an exemplary embodiment of the present application, the negative electrode slurry may include a negative electrode active material layer composition and a slurry solvent.

[0135] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy 5% or more and 40% or less.

[0136] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% or more and 40% or less, preferably 7% or more and 35% or less, and more preferably 10% or more and 30% or less.

[0137] The solid content of the negative electrode slurry may refer to the content of the negative electrode composition contained in the negative electrode slurry, and may refer to the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.

[0138] When the solid content of the negative electrode slurry satisfies the above range, the present invention has the following characteristics: since the viscosity is appropriate during the formation of the negative electrode active material layer, the negative electrode active material layer can be efficiently formed by minimizing the aggregation phenomenon of particles of the negative electrode composition.

[0139] In an exemplary embodiment of the present application, the use of the slurry solvent is not limited as long as the slurry solvent can disperse the above-mentioned negative electrode composition, but specifically, water or NMP may be used.

[0140] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.

[0141] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.

[0142] The porosity varies with the composition and content of the silicon-based active material, conductive material and binder contained in the negative electrode active material layer. In particular, when the silicon-based active material and conductive material according to the present application are contained in a specific composition and content, the above-mentioned range is satisfied, thereby being characterized in that the conductivity and resistance in the electrode have an appropriate range.

[0143] In an exemplary embodiment of the present application, a positive electrode includes: a positive electrode current collector layer; and a positive electrode active material layer disposed on one surface or both surfaces of the positive electrode current collector layer.

[0144] In an exemplary embodiment of the present application, the positive electrode active material layer includes a positive electrode active material layer composition, and the positive electrode active material layer composition may include one or more selected from a positive electrode active material, a positive electrode conductive material, and a positive electrode binder.

[0145] In the positive electrode, the positive electrode collector layer is not particularly limited as long as the positive electrode collector layer has conductivity and does not cause chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc. Alternatively, the positive electrode collector layer may generally have a thickness of 1 μm to 500 μm, and the adhesion to the positive electrode active material may also be enhanced by forming fine concavoconvexities on the surface of the positive electrode collector layer. For example, the positive electrode collector layer may be used in various forms such as a film, a sheet, a foil, a mesh, a porous body, a foam body, and a non-woven fabric body.

[0146] An exemplary embodiment of the present application provides a lithium secondary battery in which the thickness of each of the positive and negative current collector layers is 1 μm or more and 100 μm or less, and the thickness of each of the positive and negative active material layers is 20 μm or more and 500 μm or less.

[0147] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include one or more selected from the following: LiNi x Co y Mn z O2 (x+y+z=1), LiNi a Co b Mn c Al d O2(a+b+c+d=1)、LiMn2O4、LiNi 0.5 Mn 1.5 O2 and LiM x Fe y PO4 (M: transition metal, x+y=1). In this case, the positive electrode active material is not limited thereto.

[0148] Specifically, as the positive electrode active material, generally used NCM or NCMA may be used.

[0149] Typically, the positive electrode active material includes: layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or compounds substituted by one or more transition metals; lithium iron oxides such as LiFe3O4; lithium manganese oxides such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; such as the chemical formula LiNi 1-c2 M c2 O2 (wherein M is at least one selected from the following: Co, Mn, Al, Cu, Fe, Mg, B and Ga, and c2 satisfies 0.01≤c2≤0.6) represented by Ni-site lithium nickel oxide; such as the chemical formula LiMn 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (herein, M is at least one selected from the following: Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.6); LiMn2O4 in which Li in the chemical formula is partially replaced by alkaline earth metal ions, etc., but not limited thereto. The positive electrode can be Li metal.

[0150] In an exemplary embodiment of the present application, the positive electrode active material contains a lithium composite transition metal compound containing nickel (Ni), cobalt (Co) and manganese (Mn), the lithium composite transition metal compound contains single particles or secondary particles, and the single particles may have an average particle size (D 50 ).

[0151] For example, the average particle size (D 50 ) can be greater than 1 μm and less than 12 μm, greater than 1 μm and less than 8 μm, greater than 1 μm and less than 6 μm, greater than 1 μm and less than 12 μm, greater than 1 μm and less than 8 μm, or greater than 1 μm and less than 6 μm.

[0152] Even if a single particle is formed to have an average particle size (D 50 ) small particle size, the particle strength can also be excellent. For example, when the particle size is 650 kgf / cm 2 When pressed with a force of 650 kgf / cm, a single particle can have a particle strength of 100 to 300 MPa.2 The phenomenon of increasing the number of particles in the electrode due to particle breakage is also alleviated by strongly rolling single particles, thereby improving the service life characteristics of the battery.

[0153] The single particle may be prepared by mixing a transition metal precursor and a lithium raw material and firing the resulting mixture. The secondary particle may be prepared by a different method from the single particle, and its composition may be the same as or different from that of the single particle.

[0154] The method of forming single particles is not particularly limited, but generally speaking, single particles can be formed by increasing the firing temperature to achieve overfiring, and single particles can be prepared by using additives such as grain growth promoters that assist overfiring or changing the starting materials.

[0155] For example, firing is performed at a temperature at which a single particle can be formed. In order to form a single particle, it is necessary to fire at a temperature higher than that in the preparation of the secondary particles, and for example, when the composition of the precursor is the same, it is necessary to fire at a temperature of about 30°C to 100°C higher than that when the secondary particles are prepared. The firing temperature for forming a single particle may vary according to the metal composition in the precursor, for example, when it is desired to form a single particle with a high Ni-NCM lithium composite transition metal oxide having a nickel (Ni) content of more than 80 mol%, the firing temperature may be 700°C to 1000°C, preferably about 800°C to 950°C. When the firing temperature satisfies the above range, a positive active material containing a single particle having excellent electrochemical properties can be prepared. When the firing temperature is less than 790°C, a positive active material containing a lithium composite transition metal compound in the form of a secondary particle can be prepared, and when the firing temperature exceeds 950°C, firing may occur excessively, so that the layered crystal structure may not be formed normally, thereby deteriorating the electrochemical performance.

[0156] In this specification, single particle is a term used in the prior art to distinguish single particles from secondary particles formed by the aggregation of tens to hundreds of primary particles, and is a concept that includes single particles composed of one primary particle and quasi-single particles that are aggregates of 30 or less primary particles.

[0157] Specifically, in the present invention, the single particle may be in the form of a single particle composed of one primary particle or a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.

[0158] In an exemplary embodiment of the present application, the lithium composite transition metal compound as the positive electrode active material further includes secondary particles, and the average particle size (D 50 ) is smaller than the average particle size of the secondary particles (D 50 ).

[0159] In the present invention, the single particle may be in the form of a single particle composed of one primary particle or a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.

[0160] The lithium composite transition metal compound may further include secondary particles. Secondary particles refer to a form formed by aggregation of primary particles and can be distinguished from the concept of single particles, which include one primary particle, one single particle, or a quasi-single particle form that is an aggregate of 30 or less primary particles.

[0161] The secondary particles may have a particle size (D 50 The secondary particles may have a size of 0.05 μm 2 / g to 10 m 2 / g, preferably 0.1 m 2 / g to 1 m 2 / g and more preferably 0.3m 2 / g to 0.8 m 2 / g specific surface area (BET).

[0162] In other exemplary embodiments of the present application, the secondary particles are aggregates of primary particles, and the primary particles have an average particle size (D 50 Specifically, the secondary particles may be in the form of aggregation of several hundred primary particles, and the primary particles may have an average particle size (D ) of 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm. 50 ).

[0163] When the average particle size of the primary particles (D 50 When the average particle size of the primary particles (D 50 ) is too small, the number of primary particles that form the aggregation of lithium nickel oxide particles increases, thereby reducing the inhibitory effect of particle breakage during rolling. 50 ) is too large, the lithium diffusion path inside the primary particle becomes long, so that the resistance increases and the output characteristics may deteriorate.

[0164] According to other exemplary embodiments of the present application, the average particle size (D 50 ) is characterized by being smaller than the average particle size of the secondary particles (D 50). Therefore, even if a single particle is formed of a small particle diameter, the single particle can have excellent particle strength, and this excellent particle strength can alleviate the phenomenon that the number of fine particles in the electrode increases due to particle breakage, thereby improving the service life characteristics of the battery.

[0165] In an exemplary embodiment of the present application, the average particle size (D 50 ) is smaller than the average particle size of the secondary particles (D 50 ) as small as 1 μm to 18 μm.

[0166] For example, the average particle size (D 50 ) can be compared with the average particle size of the secondary particles (D 50 ) as small as 1 μm to 16 μm, 1.5 μm to 15 μm or 2 μm to 14 μm.

[0167] When the average particle size (D 50 ) is smaller than the average particle size of the secondary particles (D 50 ), for example, when the above-mentioned range is met, the single particle can have excellent particle strength even if it is formed with a small particle size. Therefore, the excellent particle strength alleviates the phenomenon of an increase in the number of particles in the electrode due to particle breakage, thereby having the effect of improving the service life characteristics and energy density of the battery.

[0168] According to other exemplary embodiments of the present application, the content of the single particle may be 15 to 100 parts by weight based on 100 parts by weight of the positive electrode active material. The content of the single particle may be 20 to 100 parts by weight or 30 to 100 parts by weight based on 100 parts by weight of the positive electrode active material.

[0169] For example, based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 100 parts by weight or less.

[0170] When the single particle is included within the above range, the above negative electrode material can be combined to exhibit excellent battery characteristics. Specifically, when the amount of the single particle is 15 parts by weight or more, the phenomenon of increasing the number of particles in the electrode due to particle breakage during the rolling process after manufacturing the electrode can be alleviated, thereby improving the service life characteristics of the battery.

[0171] In an exemplary embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the amount of the secondary particles may be 85 parts by weight or less based on 100 parts by weight of the positive electrode active material. Based on 100 parts by weight of the positive electrode active material, the amount of the secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less. Based on 100 parts by weight of the positive electrode active material, the amount of the secondary particles may be 0 parts by weight or more.

[0172] When the above range is satisfied, the above effect due to the presence of a single-particle positive electrode active material can be maximized. When a secondary particle positive electrode active material is included, the component may be the same as the component exemplified as the above-mentioned single-particle positive electrode active material, may be a different component, and may refer to an aggregated form of a single particle form.

[0173] In an exemplary embodiment of the present application, the content of the positive electrode active material in 100 parts by weight of the positive electrode active material layer can be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0174] The positive electrode active material layer may include, in addition to the positive electrode active material, a positive electrode conductive material and a positive electrode binder.

[0175] In this case, the positive electrode conductive material is used to provide conductivity to the electrode, and can be used without particular limitation as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery to be constructed. Specific examples thereof include: graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof may be used.

[0176] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and to improve the adhesion between the positive electrode active material and the positive electrode collector. Its specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof may be used.

[0177] The separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, and can be used without particular restrictions, as long as the separator is generally used as a separator in a secondary battery, and in particular, a separator having excellent moisture retention ability for the electrolyte and low resistance to ion migration in the electrolyte is preferred. Specifically, it is possible to use: a porous polymer film, for example, a porous polymer film formed by a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer; or a laminated structure of two or more layers thereof. In addition, a typical porous non-woven fabric, such as a non-woven fabric made of high melting point glass fiber or polyethylene terephthalate fiber, etc., can also be used. In addition, a coated separator containing a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.

[0178] Example

[0179] Hereinafter, preferred embodiments will be proposed to help understand the present invention, but these embodiments are provided only to illustrate the present invention, and it is obvious to those skilled in the art that various substitutions and variations within the scope of the present invention and the technical spirit are possible. Naturally, such substitutions and variations also fall within the scope of the appended claims.

[0180] <Preparation Example>

[0181] (1) Manufacturing of positive electrode

[0182] As the positive electrode active material, Li(Ni a Co b Mn c )O2.

[0183] In this case, the ratio of NCM other than lithium (Li) and oxygen (O2) in the positive electrode active material is Ni:Co:Mn=93:5:2, and satisfies the ratio of a:b:c=93:5:2 (a:b:c=0.93:0.05:0.02). 50 is 3.8 μm, and D min and D max The nanostructures are 1.2 μm and 13 μm respectively, and the BET specific surface area is 0.64 m 2 / g, and the true density is 4.78 to 4.80 g / cm 3 .

[0184] In addition, a positive electrode slurry was prepared by adding the positive electrode active material, the positive electrode conductive material (LB.CNT) and the binder (PVdF, KF9700) to a solvent (N-methylpyrrolidone, NMP) at a weight ratio of 97.96:0.8:1.24. The positive electrode slurry was applied to an aluminum (Al) film having a thickness of 25 μm as a positive electrode current collector, the aluminum (Al) film was dried, and then the dried aluminum (Al) film was rolled using a calender to manufacture the positive electrode.

[0185] (2) Manufacturing of negative electrode

[0186] A negative electrode active material layer composition was prepared, which contained Si (average particle size (D 50 ): 5 μm), a first conductive material, a second conductive material and polyacrylamide as a binder. A negative electrode slurry (solid concentration: 28 wt %) was prepared by adding the negative electrode active material layer composition to distilled water as a solvent for forming a negative electrode slurry.

[0187] The first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D 50 ): 3.5 μm), and the second conductive material is carbon nanotubes.

[0188] As a mixing method, after the first conductive material, the second conductive material, the binder, and water were dispersed at 2500 rpm for 30 minutes using a homomixer, the active material was added thereto, and then the resulting mixture was dispersed at 2500 rpm for 30 minutes to prepare slurry.

[0189] At 3.00 mg / cm 2 The negative electrode slurry was used to coat both surfaces of a copper current collector (thickness: 15 μm) as a negative electrode current collector, and the copper current collector was rolled and then placed in a vacuum oven and dried at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 23 μm).

[0190] (3) Manufacturing of secondary batteries

[0191] An electrode assembly was manufactured by inserting a compression-resistant thin film separator (PE 12 μm) ceramic coating 3 μm / 3 μm between the positive electrode and the negative electrode. After the electrode assembly was placed in a case, an electrolyte was injected into the case to manufacture a lithium secondary battery.

[0192] In this case, the electrolyte satisfies the composition and content shown in Table 1 below.

[0193]

[0194] Experimental Example 1: Evaluation of service life

[0195] The life of the lithium secondary battery containing the negative electrode prepared in the embodiment and the comparative example was evaluated using an electrochemical charge and discharge device, and the capacity retention rate was evaluated. The secondary battery was subjected to an in-situ cycle test at 4.2 to 3.2 V and 1C / 1C, and the capacity retention rate was measured by charging / discharging the secondary battery at 1C / 1C (4.2 to 3.2 V) every 50 cycles during the test, and the results are shown in Table 2.

[0196] Capacity retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the first cycle)} × 100

[0197] Experimental Example 2: Evaluation of resistance increase rate measurement

[0198] After measuring the capacity retention rate by charging / discharging the secondary battery at 1C / 1C (4.2-3.2 V) every 50 cycles during the test of Experimental Example 1, the resistance increase rate was compared and analyzed by discharging the secondary battery at 2.5C pulse at SOC 50 to measure the resistance, and the results are shown in Table 2 below.

[0199] Experimental Example 3: Using the bag test to measure the volume change caused by gas generation

[0200] For the lithium secondary batteries including the negative electrodes manufactured in the above-mentioned embodiments and comparative examples, a pouch cell with a capacity of 1 Ah was fully charged to 4.2 V at 0.33C and then stored in an oven at 60°C for 8 weeks. Thereafter, after being fully discharged to 2.5 V, quantitative gas analysis was performed by extracting the gas generated in the pouch cell using a GC / MS method, and the results are shown in Table 2 below.

[0201]

[0202] The electrolyte according to the present application includes a bifunctional electrolyte additive, which can be used to capture Lewis acid generated by a solvent contained in the electrolyte and form a negative electrode film when driving a lithium secondary battery. In addition, the electrolyte contains an additive containing two or more fluorine groups as an additive, thereby maintaining battery resistance and improving high temperature cycle performance.

[0203] As described above, it can be confirmed that the features of Examples 1 to 4 are that, by including a specific additive in the electrolyte, the battery resistance can be maintained when the lithium secondary battery is driven, while improving the high temperature cycle performance and reducing the amount of gas generated during storage. Specifically, Examples 1 to 3 are the cases where all the compositions and contents are the same and only the type of additive containing two or more fluorine groups is changed, and Example 4 is the case where the content of the additive in the electrolyte corresponds to the upper limit of the range according to the present application.

[0204] Comparative Examples 1 and 2 are the cases where one of the additives is not used, Comparative Example 3 is the case where the additive itself is not used, and Comparative Example 4 corresponds to the case where an excessive amount of the additive is used. In this case, when compared with the examples, it can be confirmed that the capacity retention rate is reduced, the resistance increase rate is high, and the cycle performance is deteriorated due to the generation of a large amount of gas.

[0205] Comparative Examples 5 and 6 correspond to the case where the content of the additive is appropriately less than 1 part by weight, but the proportion of the additive exceeds the scope of the present application. It can be confirmed that when compared with the embodiment, the performance is also deteriorated. That is, it can be confirmed that when the weight ratio exceeds the above ratio, the battery resistance becomes too high, and the solubility of the additive containing two or more fluorine groups is low, so when the additive containing two or more fluorine groups is used beyond the above range, the performance of the lithium secondary battery will deteriorate because dissolution occurs in the electrolyte.

[0206] Comparative Example 7 corresponds to the case where an additive with a propargyl group and a coumarin group is used to replace an additive with a cyano group and a coumarin group. In this case, it can be confirmed that when compared with the embodiment, the room temperature service life durability can be the same, but by applying a propargyl group, the initial resistance increases when compared with the application of a cyano group, thereby the performance of the lithium secondary battery deteriorates. That is, it can be confirmed that since the present application includes a specific functional group as a functional group, the specific functional group can play a role in capturing the Lewis acid produced by the solvent contained in the electrolyte and forming a negative electrode film, so the performance is better than Comparative Example 7.

Claims

1. A lithium secondary battery, comprising: a positive electrode; a silicon-based negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the silicon-based negative electrode comprises: a negative electrode current collector layer; and a negative electrode active material layer disposed on one or both surfaces of the negative electrode current collector layer, the negative electrode active material layer comprises a negative electrode active material layer composition, the negative electrode active material layer composition comprises a silicon-based active material, the silicon-based active material comprising one or more selected from SiOx where x = 0, SiOx where 0 < x < 2, SiC, and Si alloys, the electrolyte comprises an additive, the additive comprises: a bifunctional electrolyte additive; and an additive comprising two or more fluorine groups, the bifunctional electrolyte additive comprises a cyano group and a coumarin group as functional groups, and based on 100 parts by weight of the additive, the content of the bifunctional electrolyte additive is 45 parts by weight or more and 55 parts by weight or less, and the content of the additive comprising two or more fluorine groups is 45 parts by weight or more and 55 parts by weight or less.

2. The lithium secondary battery according to claim 1, wherein the silicon-based active material comprises one or more selected from SiOx where x = 0, SiOx where 0 < x < 2, and metal impurities, and based on 100 parts by weight of the silicon-based active material, the content of SiOx where x = 0 is 70 parts by weight or more.

3. The lithium secondary battery according to claim 1, wherein based on 100 parts by weight of the negative electrode active material layer composition, the content of the silicon-based active material is 60 parts by weight or more.

4. The lithium secondary battery according to claim 1, wherein the electrolyte further comprises one or more selected from a solvent and a lithium salt.

5. The lithium secondary battery according to claim 1, wherein based on 100 parts by weight of the electrolyte, the content of the additive is 5 parts by weight or less.

6. The lithium secondary battery according to claim 1, wherein the weight ratio of the bifunctional electrolyte additive to the additive comprising two or more fluorine groups is 1:

1.

7. The lithium secondary battery according to claim 1, wherein the additive comprising two or more fluorine groups is a lithium borate comprising two or more fluorine groups or a lithium phosphate comprising two or more fluorine groups.

8. The lithium secondary battery according to claim 4, wherein the solvent is a carbonate-based mixed solvent.

9. The lithium secondary battery according to claim 1, wherein the positive electrode comprises: a positive electrode current collector layer; and a positive electrode active material layer disposed on one or both surfaces of the positive electrode current collector layer, the positive electrode active material layer comprises a positive electrode active material layer composition, the positive electrode active material layer composition comprises a positive electrode active material, and The positive electrode active material comprises one or more selected from the following: LiNi x Co y Mn z O2 (x+y+z=1), LiNi a Co b Mn c Al d O2(a+b+c+d=1)、LiMn2O4、LiNi 0.5 Mn 1.5 O2 and LiM x Fe y PO4 (M: transition metal, x+y=1).

10. The lithium secondary battery according to claim 1, wherein the thickness of each of the positive electrode current collector layer and the negative electrode current collector layer is 1 μm or more and 100 μm or less, and the thickness of each of the positive electrode active material layer and the negative electrode active material layer is 20 μm or more and 500 μm or less.

Citation Information

Patent Citations

  • Anode for lithium ion battery

    JP2009080971A